Management Outcome of Burn Injury and Associated Factors among Hospitalized Children at Ayder Referral Hospital, Tigray, Ethiopia - Sielu Alemayehu; Bhafta Afera; Kalayou Kidanu; Tilahun Belete (International Journal of Pediatrics)
Background. Burn injuries are a global public health problem, accounting for an estimated 265,000 deaths. Globally, over half of the disability-adjusted life years lost from fire-related burns which occurred between the ages of 0 and 14 years. The rate of child deaths from burns is currently over 7 times higher in low- and middle-income countries than in high-income countries. In Ethiopia, burn was the second leading cause of death among children from the unintentional injuries. So far, no research had been conducted in terms of assessing the outcome of burn injury in children in Ethiopia and particularly in Tigray region. The aim of this study was to assess the outcome of burn injury and associated factors among hospitalized children of under 18 years at Ayder Referral Hospital in Mekelle, Ethiopia. Method. A retrospective document review was used to assess the outcome of burn injury and associated factors in Ayder Referral Hospital. A total of 382 hospitalized children’s chart from 2011 to 2015 were reviewed using a structured check list. To select the patients’ chart, a simple random sampling technique was used and a sampling frame was prepared based on a registration book. Data was entered, cleaned, and analyzed using SPSS version 20. Result. Almost 70% of the burns were caused by scald, and 45.3% of the burns were confined to the upper extremities. Eighty-two percent of the patients were discharged without complication. Lack of fluid resuscitation within 24 hours (AOR=2.767; 95% CI (1.276-5.999)) and a burn patient with malnutrition (AOR=0.252; 95% CI (0.069-0.923)) were statically significant with the outcome of burn injury. Conclusion. Majority of the pediatric burn patients were discharged without complication. The most causative agent of these accidents was scald; upper extremities also were the most affected area. The factors associated with the outcome of burn injury according to this study were lack of fluid resuscitation and malnourishment of burn patients.